Evaluating the spread of stony coral tissue loss disease in the Bay Islands, Honduras - Truc, Mar; Rivera, Antonella; Ochoa, Gabriela M.; Dueñas, Damaris; Guifarro, Zara; Brady, Gisselle; Zúniga, Zara; Gutiérrez, Braulio; Chock, Caitlin; Zaldivar, Laura (Frontiers in Marine Science, 2023)
Scleractinian corals, considered key reef ecosystem engineers, have suffered irreparable damage over the last decades, with causes widely attributed directly and indirectly to increased human pressure on coral communities. Stony coral tissue loss disease (SCTLD), first detected in Florida in 2014, by early 2023 had spread to 26 jurisdictions in the wider Caribbean, causing severe effects on coral reefs. In January 2020, monitoring efforts to detect SCTLD began on the island of Roatan in Honduras. The disease was first reported in Flowers Bay, Roatan, in September 2020. Since, dedicated collaborative efforts have been made to assess the severity of the disease, mitigate its effects, and raise coral reef conservation awareness. To track the progression of the outbreak, presence-absence data were collected using the rover diver methodology. With at least 28 species affected, SCTLD has spread across the Bay Islands over a period of 13 months. Roatan and Utila have been the most impacted islands, with the disease encircling them rapidly at a rate of approximately 155 m/day. The spread of SCTLD was overall rapid, but geographical patterns were detected in Roatan, where it showed faster progression on the windward side than on the leeward side. Further research is required to explore whether these disparities are related to marine traffic, water quality, currents, or a combination of multiple factors. Our findings shed new knowledge on the spread of SCTLD in Honduras, which can provide insights for other Caribbean nations whose economies are also dependent on the health of their coral reefs.